Analisis Kemampuan Calon Guru dalam Menyusun Lembar Kerja Peserta Didik yang Membangun Keterampilan Abad 21 - Sridana, Nyoman; Sukarma, I Ketut; Samsuri, Taufik; Gunawan, Rendi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Students who are prospective teachers must adapt to the development of digital technology, especially its use in education. They are taught teaching practices with their peers before going directly into the field, as well as how to create learning tools. This research aims to analyze the ability of prospective teachers to develop student worksheets (LKPD) that foster 21st-century skills. This study is a qualitative descriptive research involving 14 student teachers as subjects. Data collection was conducted using assessment sheets. The results of the study indicate that (1) the LKPD created by the prospective teachers had an average score of 3.28, categorized as high; (2) the critical thinking aspect had an average score of 3.32, categorized as high; communication had an average score of 3.41, categorized as high; collaboration had an average score of 3.45, categorized as high; and creativity and innovation had an average score of 2.95, categorized as moderate. This shows that the prospective teachers are quite proficient in developing LKPD that build 21st-century skills.